The Effectiveness of Technical Standards in Climate Disaster Prevention and Mitigation: The Case of the 2024 Flood in Porto Alegre - Wendling, Júlia Katiély dos Santos; Silva, Thaísa Leal da (Technical and Scientific Journal Green Cities, 2025)
Objective – To analyze the effectiveness of applying the technical standards NBRs ISO 37120, 37122, and 37123 in preventing, mitigating, and responding to the impacts of the May 2024 flood in Porto Alegre-RS, considering the normative indicators of urban services, resilience, and quality of life in the face of the empirical reality of the disaster.Methodology – Case study with a qualitative approach, based on documentary analysis and critical application of normative indicators.Originality/Relevance – The study fills a gap by linking international standards for sustainable and resilient cities with recent extreme climate events in the context of Rio Grande do Sul.Results – Disparities were highlighted between formal indicators and the real urban response capacity of Porto Alegre-RS in the face of climate disasters.Theoretical/Methodological Contributions – The research proposes an integrated reading of normative indicators as diagnostic instruments and not just technical compliance instruments.Social and Environmental Contributions – The findings highlight the need for territorialized and participatory public policies to strengthen urban socio-environmental resilience.
Keywords: Urban resilience; Normative indicators; Urban flooding